DETEKSI BAKTERI GENUS VIBRIO SEBAGAI CAUSATIVE AGENT PADA IKAN LELE SANGKURIANG (CLARIAS GARIEPINUS VAR. SANGKURIANG) DI KOTA TASIKMALAYA - Meylani, Vita; Putra, Rinaldi Rizal (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2018)
Sangkuriang catfish (Clarias gariepinus var Sangkuriang) is the main commodity that widely cultivated in Tasikmalaya City. However, farmers have difficulty because of the disease which causes death in fish. High mortality is suspected as a vibriosis disease by genus Vibrio because redness wounds on dead fish. The purpose of this study is to know the genus Vibrio which causes of disease in Sangkuriang catfish. 10 samples of fish were taken from Sangkuriang catfish pond culture in Kelurahan Kersanagara Tasikmalaya City which were potentially suspected of vibriosis disease. Isolation of bacteria were done on TCBS medium. Bacterial isolates were collected from fish lesion on the body surface, liver, and kidneys of catfish. Isolation were able to gained 21 isolates and then 5 isolates (VK1, VK5, VK7, VK17, and VK21) were selected based on colony morphology and Postulates Kochâs were tested. The results showed that the clinical symptoms of catfish infected by vibriosis were redness lesions/ulcers on the body surface, hemorrhagic, fluid inside stomach, and fin eroded with redness wound. Bacterial identification through biochemical test revealed the causative agent of catfish disease at brackish pond area were bacteria of the genus Vibrio (VK 1, VK 5, and VK 7), Vibrio vulnificus (VK 17 and VK 21).